Emerging role of extracellular microRNAs and lncRNAs - Geyu Zhou; Xi Chen (ExRNA)
Abstract The discovery of extracellular non-coding RNAs, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), has dramatically altered our understanding of the role RNA plays in organisms. Importantly, these extracellular miRNAs and lncRNAs are promising noninvasive biomarkers for diagnosis and prognosis of pathological status. Extracellular vesicles (EVs) are natural carriers of secreted extracellular miRNAs and lncRNAs. Although knowledge regarding the biologically relevant role of extracellular miRNAs is expanding, whether extracellular lncRNAs play a similar role remains incompletely understood. Here, we review the current knowledge regarding extracellular miRNAs and highlight a recent advance demonstrating that extracellular lncRNAs may also mediate cell-to-cell communication and other complicated biological processes.